Enantioselective Heterogeneous Heck–Matsuda Reaction with Polymer-Supported PyOx Ligands - Herrera, Christian L.; Oliveira, Rafael L.; Silva, Rodrigo C.; Correia, Carlos R. D.; Pastre, Julio C. (Synlett, 2024)
Carboxymethyl C5-functionalized pyridine-oxazoline (PyOx) ligands are immobilized onto Merrifield and Wang resins utilizing three distinct strategies. The immobilized PyOx ligands are employed in the Pd-catalyzed heterogeneous Heck–Matsuda reaction for the desymmetrization of 3-cyclopenten-1-ol, resulting in the production of 20 examples of aryl-penten-1-ols with yields reaching up to 87%, and enantiomeric ratios ranging between 90:10 and 99:1. These outcomes align with those achieved by the homogeneous counterparts, demonstrating comparable efficiency. Subsequent recycling analysis reveals a progressive decline in catalyst efficiency upon reuse, suggesting the formation of palladium black on the catalyst surface.
Keywords: heterogeneous catalysis; enantioselective Heck–Matsuda; pyridine-oxazoline; polymer-supported ligand; Merrifield resin